Comparison of nutritional compositions and heavy metals analysis between wild and farmed Tilapia (Oreochromis sp.) and Asian Seabass (Lates sp.) in Sabah, Malaysia - Lennon Glenn Francis; Mohd Fareed Aming; Shariffa Ishaziah Mohd Idris; Nurzafirah Mazlan; Rafidah Othman; Ching Fui Fui @ Faihana Ching Abdullah; Rossita Shapawi; Muhammad Dawood Shah (Academic Press, 2024)
In Sabah, Malaysia, Tilapia and Asian seabass are culturally and economically important seafood choices. Understanding their nutritional content and contaminants, both wild-caught and farmed, is crucial as demand increases. This study aimed to analyze the proximate composition and heavy metals concentrations in Tilapia and Asian Seabass fish flesh, and compare the wild-caught and farmed samples. The results revealed significant nutritional variations between the two groups. Wild-caught Tilapia exhibited higher protein content (16.90 ± 0.50 %), carbohydrate levels (0.7 ± 0.10 %), moisture (80.25 ± 0.58 %), and ash content (9.22 ± 1.27 %) while farmed Tilapia displayed elevated fat content (3.55 ± 0.05 %) and energy values (94.5 kcal per 100 g). Iron concentrations in both wild and farmed Tilapia remained within safe limits for human consumption and Zinc was detected in wild Tilapia only. Meanwhile, the farmed Asian Seabass demonstrated higher protein (18.45 ± 0.25 %), fat (0.9 ± 0.10 %), carbohydrate (0.8 ± 0.20 %), ash content (21.04 ± 2.1 %), and energy values (85.5 kcal per 100 g) compared to the wild. Further study can be conducted to study the benefits of these fish species to human health upon consumption.